Physicochemical Characteristics of Gum Arabic From Acacia mearnsii Grown in Alahan Panjang, West Sumatera - Syukriani, Lily; Yunita, Roza; Rosadi, Firsta Ninda; Jamsari, Jamsari (AGROSCRIPT: Journal of Applied Agricultural Sciences, 2024)
Acacia gum produced from Acacia mearnsii is a natural material with great potential for various industrial applications due to its unique physicochemical properties. This study aimed to characterize gum acacia from Alahan Panjang, West Sumatra. Characterizatio was done using Fourier Transform Infrared Spectroscopy (FTIR), X-ray fluorescence (XRF), and X-ray diffraction (XRD) techniques. FTIR results revealed the presence of hydroxyl (-OH), carbonyl (-C=O), and glycosidic (C-O-C) groups, indicating the complex polysaccharide structure of the gum. XRF analysis showed the dominance of calcium oxide (CaO) with a concentration of 81.652%, followed by potassium oxide (K₂O) at 10.052% and phosphate (P₂O₅) at 6.341%. Meanwhile, the XRD diffraction pattern identified a near amorphous diffraction with some weak crystalline peaks. This combination of results suggests that gum acacia has chemical and physical properties that support its use as an emulsifier, thickener, and filler in various industries, such as food, pharmaceutical, and cosmetics.